Rev. Prof. Radosław Chałupniak and His Scholarly Contribution to the Development of Catechetics - Zellma, Anna (Studia Warmińskie, 2022)
Rev. Prof. Radosław Chałupniak (1967-2020) was an outstanding Polish catechetical scholar. Professionally associated with the University of Opole, he collaborated with various academic milieus in Poland and abroad (including Austria, Germany, Malta, Italy, Czechia). He was a pioneer of innovative solutions in aesthetic education as he took advantage of painterly masterpieces to see them applied in school catechesis; first and foremost, however, he was an extraordinary person and priest: open, friendly, kind, a man devoted to God, the Church and other people, gifted with charisma and creative spirit. His studies focused mainly on school and parish catechesis. Much of his research concerned the concepts in religious education and parish catechesis in European countries (especially in Germany) as well as various aspects of religious education in Poland and abroad. He recognized and argued the rationale behind the crucial role of masterpieces of painting in the religious education of children and adolescents. Chałupniak also drew attention to various organizational, substantive and methodical aspects of catechesis in the family, school and parish. In the final years of his scholarly career, the Reverend Professor aptly recognized the signs of the times and undertook analyses of the “virtual world”, which plays an important role in evangelization, catechization and education of the young generation. The paper first discusses the figure of Rev. R. Chałupniak. Subsequently, following an analytical overview of his principal publications, it outlines the substantive scope of his scientific inquiry and involvement in the search for the shape of contemporary integral catechesis in various educational environments, particularly in the family, school and parish. The author underscores Rev. R. Chałupniak’s contribution to the development of Polish integral catechetics, which translates into a truly impressive achievement in terms of both quality and quantity.